Variations of total electron content during quiet and disturbed geomagnetic conditions over Malaysia - Sadia, Mostofa; Mardina, Abdullah; Mohamad Tariqul, Islam; Siti Aminah, Bahari; Ahmmed, Mohammad Badal (Institute of Electrical and Electronics Engineers Inc., 2022)
Ionosphere behavior is characterized by geographical and temporal changes. It was possible to determine the mobility of the ionosphere by observing how the total electron content (TEC) changed over time. The study on TEC variation was conducted in 2008 and 2009 over Malaysia, where latitude ranged from 1° N to 8° E and longitude ranged from 95° to 120° E, with each year reflecting the same degree of solar activity. The hourly mean vertical TEC (VTEC) is used to monitor the difference of the TEC under various geomagnetic factors such as disturbance storm time (Dst), planetary 3-hour range index (Kp), and solar flux F10.7 variations. This paper considers four cases of geomagnetic disturbances were considered 9 March, 27 March, 4 September 2008, and 22 July 2009. A percentage deviation was calculated to further analyze the geomagnetic disturbances in the equatorial region on quiet days. Results showed the TEC during geomagnetic disturbances was lower than the quiet day, with the percentage deviations between -20% and 10%. An increment of TEC was shown after approximately 24 hours, which is in the storm recovery phase. Also found were that GPS-TEC reaches its highest around post noon and its lowest in the small hours of the morning.